2015
DOI: 10.3389/fphar.2015.00093
|View full text |Cite
|
Sign up to set email alerts
|

The acute and sub-chronic effects of cocoa flavanols on mood, cognitive and cardiovascular health in young healthy adults: a randomized, controlled trial

Abstract: Cocoa supplementation has been associated with benefits to cardiovascular health. However, cocoa's effects on cognition are less clear. A randomized, placebo-controlled, double-blind clinical trial (n = 40, age M = 24.13 years, SD = 4.47 years) was conducted to investigate the effects of both acute (same-day) and sub-chronic (daily for four-weeks) 250 mg cocoa supplementation on mood and mental fatigue, cognitive performance and cardiovascular functioning in young, healthy adults. Assessment involved repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(135 citation statements)
references
References 44 publications
6
125
0
4
Order By: Relevance
“…Another study found that daily cocoa consumption for 8 weeks can improve specific aspects of cognitive performance in a group of cognitively intact older adults [11]. The third study, conducted to investigate the effects of both acute and sub-acute (four-weeks) Theobroma cacao seed extract on mood and mental fatigue, cognitive performance and cardiovascular functioning in young, healthy adults, could find no benefit for the supplementation with this cocoa extract [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that daily cocoa consumption for 8 weeks can improve specific aspects of cognitive performance in a group of cognitively intact older adults [11]. The third study, conducted to investigate the effects of both acute and sub-acute (four-weeks) Theobroma cacao seed extract on mood and mental fatigue, cognitive performance and cardiovascular functioning in young, healthy adults, could find no benefit for the supplementation with this cocoa extract [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to acknowledge that most studies evaluated the cognitive effects of chocolate, cocoa supplements, or cocoa flavonoids given as acute [5][6][7][8] and sub-acute [8][9][10][11] administration. On the other hand, several epidemiological studies looked at the potential benefits of antioxidants in general or flavonoid-rich foods on cognitive decline or the risk for dementia [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…If this is true then the potential effects of cocoa flavanols on mood and cognitive performance may be underestimated when cocoa is co-consumed with dairy products. Only one other study has examined cocoa in the absence of dairy or calories and it was found that the consumption of tablets containing 250 mg cocoa transiently improved selfreported mental fatigue and serial sevens performance compared to placebo [17].…”
Section: Introductionmentioning
confidence: 99%
“…There is a small but growing body of research on the cognitive and mood consequences of chocolate and cocoa consumption [17,[20][21][22][23]; however, there appear to be only a few studies concerning the influence of the consumption of cocoa flavanols per se on acute changes in cognitive performance or mood. One experiment found that, compared to white chocolate containing trace amounts of flavanols, the consumption of dark chocolate containing 773 milligrams (mg) of cocoa flavanols improved spatial memory and reaction time during the predictable phase of an attention task performed 2 to 2.75 h (hrs) post-consumption [24].…”
Section: Introductionmentioning
confidence: 99%
“…Small RCTs have shown enhanced denate gyrus function in healthy 50‐ to 69‐year‐olds, measured by cognitive tests after a cocoa flavanol containing diet for 3 months; increased brain perfusion in subjects (age 50–65 years) after intake of 494 mg of cocoa flavanols; and increased blood flow velocity in the middle cerebral artery after 1 and 2 weeks of cocoa flavanol intake by healthy subjects (mean age 72 years; Dominguez & Barbagallo, ). Other RCTs also provide supportive data to conclude benefits of cocoa flavanols on cognitive functions, including in healthy young adults and in elderly people with MCI (Massee et al, ; Sokolov et al, ). However, not all studies have concluded such effects, with a flavonoid‐rich diet (in placebo groups) suggested to explain the lack of efficacy in some RCTs (Scholey & Owen, ).…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 84%